Pelatihan Menulis Essai Bagi Santri di Pondok Pesantren Taqwimul Ummah Jemur Ngawinan Wonocolo Surabaya - Djuaini, Achmad; Arisandi, Yusuf (Universitas Islam Internasional Darullughah Wadda'wah, 2023)
Santri are a group of people who live in Islamic boarding schools to learn the Koran. In the contemporary era, students can develop themselves by studying various sciences, including the world of writing. However, the reality shows that students at the Taqwimul Ummah Islamic Boarding School are involved in learning to write and only recite the Koran. The aim of this training is to equip students to have writing skills. This event presents trainers who are competent in essay writing. The activity is carried out in the form of a briefing and is immediately followed by essay writing practice. The provision consists of delivering material that introduces essay writing, the structure of essay writing, and the steps for writing an essay. Then the students receive an assignment to write an essay, which is submitted. Essay writing from students selected from the best works to be awarded.